Biocompatible conjugated porphyrin nanoparticles with photodynamic/photothermal performances in cancer therapy. (November 2020) - Yang, Lixia; Zhou, Ji; Wang, Zejiang; Li, Haolan; Wang, Kai; Liu, Hui; Wu, Fengshou
Abstract: Phototherapy has emerged as a promising way to treat cancer with high selectivity and non-invasiveness. With a vision towards solving the safety problems of current inorganic materials, tremendous efforts have been dedicated to search for much safer and more efficient organic nanoagents for cancer phototherapy. Herein, we design and synthesize a new porphyrin compound (TPAPor) by covalent conjugation of porphyrin and triphenylamine. The typical donor-acceptor-donor (D-A-D) structure of TPAPor facilitates the red-shift of absorption to the near-infrared (NIR) region. Subsequently, the amphiphilic organic molecule is self-assembled into nanoparticles (TPAPor NPs) with homogeneous size (about 80 nm), enhanced NIR absorption and excellent biocompatibility. TPAPor NPs display low singlet oxygen ( 1 O2 ) generation and excellent photothermal conversion efficiency (55.7%) under irradiation of a single NIR laser (690 nm). Moreover, TPAPor NPs could ablate the HeLa cells by NIR laser-induced ROS and heat generation, with the half maximal inhibitory concentrations (IC50 ) about 18.3 μg/mL. This study indicates TPAPor NPs are promising nanoagents for cancer therapy through photothermal/photodynamic combination manner. Graphical abstract: Image 1 Highlights: Conjugated porphyrin (TPAPor) with D-A-D structure was synthesized and characterized. TPAPor could self-assemble into nanoparticles (TPAPor NPs) with high photothermal conversion efficiency. TPAPor NPs could ablate cancer cells under NIR laser irradiation with high phototoxicity.